A trade-off between having many sons and shorter maternal post-reproductive survival in pre-industrial Finland - Helle, Samuli (The Royal Society, 2013)
A bias in reproduction towards sons, which are energetically more costly than daughters, has been suggested to shorten parental lifespan, but previous results have been mixed. Reproductive costs should be most evident in low rather than high resource settings, and are not expected to be severe in men, because women pay higher direct costs of reproduction. We, therefore, used demographic data from pre-industrial Finland to investigate whether the number of sons and daughters born affected their parents’ post-reproductive survival and whether this was related to parent's resource availability. Irrespective of access to resources, mothers, but not fathers, with many sons suffered from reduced post-reproductive survival, and this association decreased as mothers aged. Our results provide evidence that Finnish mothers traded long post-reproductive lifespan for giving birth to many sons.